Pengaruh Anestesi Spinal Terhadap Hemodinamik Pada Pasien Sectio Caesarea di Rumah Sakit Umum Cut Meutia Aceh Utara - Saiful Nazar; Tophan Heri Wibowo; Ikit Netra Wirakhmi (Viva Medika, 2023)
Hemodynamic changes are a risk that can occur in the use of spinal anesthesia in sectio caesarea operations. The aim of this study was to determine the effect of spinal anesthesia on hemodynamics in sectio caesarea patients at Cut Meutia Hospital, North Aceh. This research method uses observational analytic with cross sectional with pretest & posttest only group. The sampling technique was carried out by means of a total sampling of 70 respondents. The research instrument that will be used in this study is the patient observation sheet. Data analysis was performed univariately and bivariately using the Wilcoxon test. The results showed that there were differences in hemodynamics (blood pressure) before and after spinal anesthesia in sectio caesarea patients with a p-value of 0.000 (p<0.05). There were differences in hemodynamics (pulse) before and after spinal anesthesia in sectio caesarea patients with a p-value of 0.000 (p <0.05). This study concluded that there was an effect of spinal anesthesia on hemodynamics in sectio caesarea patients at Cut Meutia Hospital, North Aceh